CYP4 subfamily V member 2 (CYP4V2) polymorphisms were associated with ischemic stroke in Chinese Han population - Faqing Long; Desheng Wang; Qingjie Su; Yuhui Zhang; Jianhong Li; Shiliang Xia; Hailun Wang; Yongping Wu; Qiumin Qu (BMC Medical Genomics, 2022)
Abstract Background CYP4 subfamily V member 2 (CYP4V2) polymorphisms are related to venous thromboembolism. However, the influence of CYP4V2 polymorphisms on the susceptibility to ischemic stroke (IS) remains undetermined. Methods We selected and genotyped five polymorphisms of CYP4V2 in 575 cases and 575 controls to test whether CYP4V2 variants were associated with the risk for IS in a Chinese Han population. Genotyping of CYP4V2 polymorphisms was performed using the Agena MassARRAY platform. Logistic regression analysis was used to assess the association between CYP4V2 polymorphisms and IS risk by calculating odds ratios (ORs) and 95% confidence interval (CI). False-positive report probability analysis was applied to assess the noteworthy relationship of the significant findings. Results CYP4V2 rs1398007 might be a risk factor for IS (OR = 1.34, 95% CI 1.05–1.71, p = 0.009). Specially, confounding factors (age, gender, smoking and drinking status) might affect the relationship between rs1398007 and IS susceptibility. Moreover, rs1053094 and rs56413992 were associated with IS risk in males. Multifactor dimensionality reduction analysis showed the combination of rs13146272 and rs3736455 had the strongest interaction effect (information gain value of 0.40%). Furthermore, genotypes of rs1398007 (p = 0.006) and rs1053094 (p = 0.044) were associated with the levels of high-density lipoprotein cholesterol (HDL-C) among healthy controls. Conclusion Our results first provided evidence that CYP4V2 rs1398007 might be a risk factor for IS, which provides instructive clues for studying the mechanisms of CYP4V2 to the pathogenesis of IS.